Meningkatkan Keterampilan Bercerita dengan Metode Kamishibai - Segu Atio (AT-TURATS, 2016)
This quantitative research using quasi-experimental method aims to examine whether the kamishibai method is effective in improving the storytelling skills in English. As for the research design used was one group pretest posttest. To fnd out about the response of subjects in the study regarding the method of kamishibai, the researcher also distributed questionnaires. The results of the research indicated that based on the statistical calculation using formula of the paired samples t-test, the kamishibai method was effective in improving the students’ storytelling ability; and based on the responses of the respondents upon being tabulated, it was known that the majority of respondents (70%) agreed that the kamishibai method helps them to tell stories better than before. The average score of the tabulated responses of the respondents was 41 falling within the interval of 37–45, which means that the average respondent agreed with the effectiveness of the use of kamishibai method to improve the ability of storytelling in the English.